2011
DOI: 10.1186/1465-9921-12-124
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of quantitative proteomics on asthmatic bronchi: effects of inhaled glucocorticoid treatment

Abstract: BackgroundProteomic studies of respiratory disorders have the potential to identify protein biomarkers for diagnosis and disease monitoring. Utilisation of sensitive quantitative proteomic methods creates opportunities to determine individual patient proteomes. The aim of the current study was to determine if quantitative proteomics of bronchial biopsies from asthmatics can distinguish relevant biological functions and whether inhaled glucocorticoid treatment affects these functions.MethodsEndobronchial biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Though asthma classification was not attempted, important associations between subgroups of protein classes like Toll-like receptors and chemokines were demonstrated. Recently, networks have also been used to determine if quantitative proteomics of bronchial biopsies from asthmatics can distinguish biological functions [32]. Though networks analyses are finding increasing use in the published literature to analyze a wide range of scientific data such as social networks, occurrence of comorbidities and gene–gene interactions [33•], these unipartite analyses show only one part of a bipartite (eg, subject–cytokine) relationship.…”
Section: Network Analysis Methodsmentioning
confidence: 99%
“…Though asthma classification was not attempted, important associations between subgroups of protein classes like Toll-like receptors and chemokines were demonstrated. Recently, networks have also been used to determine if quantitative proteomics of bronchial biopsies from asthmatics can distinguish biological functions [32]. Though networks analyses are finding increasing use in the published literature to analyze a wide range of scientific data such as social networks, occurrence of comorbidities and gene–gene interactions [33•], these unipartite analyses show only one part of a bipartite (eg, subject–cytokine) relationship.…”
Section: Network Analysis Methodsmentioning
confidence: 99%
“…These authors used pathway analysis to identify biologically important functional pathways including acute phase response, cell-cell signalling and tissue development in asthmatic airways compared with controls. 69 Hamsten et al also demonstrated alterations in CCL5 plasma protein levels with significantly lower levels reported in children with persistent asthma compared with controls. 70 Wu et al used LC-MS/MS of BALF samples after allergen challenge in asthma patients to describe the complex biological pathways activated in the lung.…”
Section: Asthmamentioning
confidence: 92%
“…A further study of endobronchial biopsies in a small number of asthma patients and healthy volunteers using MS also identified CCL5 as a biomarker. These authors used pathway analysis to identify biologically important functional pathways including acute phase response, cell–cell signalling and tissue development in asthmatic airways compared with controls . Hamsten et al .…”
Section: Proteomic Applications In Respiratory Diseasementioning
confidence: 99%
“…It is possible to use omics data analysis to assess the global effect of anti-asthma drug administration. O'Neil and collaborators used quantitative proteomics on asthmatic bronchi to investigate the effects of inhaled glucocorticoid treatment (72). The authors carried out a double-blind treatment experiment with either placebo or budesonide (800 μg daily for 3 mo) on a cohort of 15 subjects, of which 12 were patients with asthma.…”
Section: The "Omics" Approach With Data Analysismentioning
confidence: 99%